Analisis Laba dan Arus Kas Dalam Memprediksi Financial Distress (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar di BEI Periode 2016-2018) - Dian Lestari; Debbi Chyntia Ovami; Reza Hanafi Lubis (Journal of Trends Economics and Accounting Research, 2022)
This research aimed to determine the ability of profit and cash flow in predicting the financial distress at the BEI-registered banking company. This type of research was a qualitative descriptive, the technique of data collection was by observation, the data used was the financial statements for 3 years starting from 2016 until the year 2018. The variables used in this study were income, cash flows and financial distress. The results showed that a better profit variable was used in predicting the financial distress in the upcoming 1 year compared to the cash flow variable